Surgery for Dupuytren's contracture of the fingers. - Rodrigues, J; Becker, G; Ball, C; Zhang, W; Giele, H; Hobby, J; Pratt, A; Davis, T (Cochrane Collaboration, 2015)
Dupuytren's disease is a benign fibroproliferative disorder that causes the fingers to be drawn into the palm via formation of new tissue under the glabrous skin of the hand. This disorder causes functional limitations, but it can be treated through a variety of surgical techniques. As a chronic condition, it tends to recur. Objectives:To assess the benefits and harms of different surgical procedures for treatment of Dupuytren's contracture of the index, middle, ring and little fingers.